Focused ultrasound for immuno-adjuvant treatment of pancreatic cancer: An emerging clinical paradigm in the era of personalized oncotherapy. (2nd November 2017) - Maloney, Ezekiel; Khokhlova, Tanya; Pillarisetty, Venu G.; Schade, George R.; Repasky, Elizabeth A.; Wang, Yak-Nam; Giuliani, Lorenzo; Primavera, Matteo; Hwang, Joo Ha
ABSTRACT: Current clinical treatment regimens, including many emergent immune strategies (e.g., checkpoint inhibitors) have done little to affect the devastating course of pancreatic ductal adenocarcinoma (PDA). Clinical trials for PDA often employ multi-modal treatment, and have started to incorporate stromal-targeted therapies, which have shown promising results in early reports. Focused ultrasound (FUS) is one such therapy that is uniquely equipped to address local and systemic limitations of conventional cancer therapies as well as emergent immune therapies for PDA. FUS methods can non-invasively generate mechanical and/or thermal effects that capitalize on the unique oncogenomic/proteomic signature of a tumor. Potential benefits of FUS therapy for PDA include: (1) emulsification of targeted tumor into undenatured antigens in situ, increasing dendritic cell maturation, and increasing intra-tumoral CD8 + / T regulatory cell ratio and CD8 + T cell activity; (2) reduction in intra-tumoral hypoxic stress; (3) modulation of tumor cell membrane protein localization to enhance immunogenicity; (4) modulation of the local cytokine milieu toward a Th1-type inflammatory profile; (5) up-regulation of local chemoattractants; (6) remodeling the tumor stroma; (7) localized delivery of exogenously packaged immune-stimulating antigens, genes and therapeutic drugs. While not all of these results have been studied in experimental PDA models to date, the principles garnered from other solid tumor and disease models have direct relevance to the design of optimal FUS protocols for PDA. In this review, we address the pertinent limitations in current and emergent immune therapies that can be improved with FUS therapy for PDA.